Тhe influence of etoxidol upon the indications of functional activity and lipid erythrocytes exchange at endotoxicosis - A P Vlasov; G A Drozdova; V F Mustyatsa; T V Tarasova; E I Nachkina; N U Leschankina (RUDN Journal of Medicine, 2010)
The chronical experiments on stray dogs at the peritonitis modeling showed the etoxidol application at a complex therapy is conducive to the improvement of erythrocytes functional activity and to the correction of lipid distress syndrome. The etoxidol lipid regulating effect is shown to take place at the expense of a decrease in the process of lipid peroxidation, as well as at the phospholipasae activity, the lipid regulating effect being evident since the first days of etoxidol application.